2007
DOI: 10.1097/blo.0b013e31803dcd6b
|View full text |Cite
|
Sign up to set email alerts
|

ACL Reconstruction

Abstract: From individual randomized studies, it is unclear whether patellar tendon grafts or hamstring tendon grafts yield the best functional results after ACL reconstruction. Therefore, we performed a meta-analysis to provide quantitative data to compare patellar with hamstring grafts after ACL reconstruction with regard to knee function. We searched computerized databases for randomized controlled trials reporting one of the following outcomes related to function: final overall International Knee Documentation Commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(83 citation statements)
references
References 32 publications
2
76
1
4
Order By: Relevance
“…Clinical outcomes are, however, far from optimal, with one third of patients experiencing residual knee laxity and over 60% with disturbances in knee function [7]. Our study confirmed such observations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Clinical outcomes are, however, far from optimal, with one third of patients experiencing residual knee laxity and over 60% with disturbances in knee function [7]. Our study confirmed such observations.…”
Section: Discussionsupporting
confidence: 85%
“…However, clinical analyses show that one third of subjects undergoing ACL reconstruction (ACLR) have residual instability at follow-up and never reach the pre-injury activity level [7]. Data on whether accompanying knee injuries substantially affect patients’ outcome are not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, ACLR is perceived to be a successful procedure; however, critical analysis has shown that clinical outcomes are less than optimal, as a recent meta-analysis has shown that normal knee function is restored in only 37% of patients undergoing ACLR [9]. Understanding which physical or psychological impairments contribute most significantly to disability following ACLR will assist in establishing appropriate rehabilitation programs in this patient population to ensure that functional levels are optimized following surgery.…”
Section: Introductionmentioning
confidence: 99%
“…33 Despite mechanical stabilization, surgical reconstruction of the ACL does not guarantee a return to previous levels of activity, good knee function, or the preservation of future joint health. 1, 14, 25, 35, 40, 42, 46 Because not all individuals regain optimal knee function after ACL reconstruction, 3, 8 it is critical to understand if knee function is associated with other clinical factors that may provide insight into the patient's current functional status. The International Knee Documentation Committee 2000 Subjective Knee Form (IKDC2000) has been used frequently after ACL reconstruction to measure knee function.…”
mentioning
confidence: 99%